Development Of Polymer Mechanical Properties Characteristics Using I-KAZ 4D Analysis Method. - Ramli, Mohd Irman; Nuawi, Mohd. Zaki; Mohammad Rasani, Mohammad Rasidi; Abdullah, Sharum; Fadli Ahmad, Muhamad Arif; Abdullah, Muhammad Fazrin (Universiti Teknologi Malaysia, 2018)
This study was undertaken to develop an alternative method based on signal analysis known as I-kaz 4D or I-kaz 4 channels.The aim was to characterize several mechanical properties including Poisson Ratio (PR), Vickers Hardness (VH),Yield Strength (YS),Tensile Strength (TS),Compression Strength (CS) and Fatigue Strength (FS).Specimens used are Polyoxymethylene (POM), Polyvinylchloride (PVC) and Blue Nylon MC (MC Blue).Round bar shape specimens were impacted by steel ball from different heights,20 cm to 40 cm.This test was conducted at semi-anechoic room and follow ASTM E1876 standard accordingly.4 accelerometer sensors were placed on the specimen surface to capture vibration signal produced by ball impact.Transient signals which generated from ball impact were analysed using Matlab software based on mathematical model I-kaz 4D.As a result,a correlation was found between I-kaz linear coefficient and material mechanical properties.However the errors are within acceptable range for all specimens used.It was found that average errors for Poisson Ratio = 0.69%,Vickers Hardness = 2.12%, Yield Strength = 3.20%,Tensile Strength = 2.43%, Compression Strength = 2.75% and Fatigue Strength =2.02%. It has potentiality to be used for further analysis of the respective materials.